Răspuns:
a) x = 4 ; y = 1
b) x = 3 ; y = 2
c) x = 10 ; y = 6
Explicație pas cu pas:
a)
{x+y = 5 (1)
{x-y = 3 (2)
=======
din (1) +(2) =>
2x = 8 => x = 4
y = 5-x = 5-4 => y = 1
1+4 = 5 ; 4-1 = 3
========================
b)
{2x+3y = 12
{x-2y = -1 I·2 =>
-----
{2x+3y = 12 (1)
{2x-4y = -2 (2) =>
din 1-2 => 3y+4y = 12+2 =>
7y = 14 => y = 2
x-4 = -1 => x = 3
2·3+3·2 = 6+6 = 12
3-2·2 = 3-4 = -1
===========================
c)
{³⁾x/2 + ²⁾y/3 = ⁶⁾7
{²⁾x/5 + ⁵⁾y/2 = ¹⁰⁾5 =>
-----
{3x+2y = 42 I·2
{2x+5y = 50 I·3 =>
-------
{6x+4y = 84 (1)
{6x+15y = 150 (2)
din (2)-(1) => 15y-4y = 150-84 =>
11y = 66 => y = 6
2x+5·6 = 50 => 2x = 20 => x = 10
10/2 + 6/3 = 5+2 = 7
10/5 + 6/2 = 2+3 = 5